Proceedings from the consultation ([s.n.] [S.l.], 2002)
Looks at the medical and social issues concerning the epidemic. Presents the core elements of a comprehensive workplace programme. Explores how a programme might be designed and implemented in individual workplaces.
Keywords: HIV